EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECKS (PC) DAN TIPE TEAMS ASSISTED INDIVIDUALIZATION (TAI) PADA MATERI PELUANG DITINJAU DARI GAYA BELAJAR SISWA KELAS XI IPS SMA DI KOTA SURAKARTA TAHUN PELAJARAN 2013 / 2014 - Veronica Sri Wigiyanti; Budiyono Budiyono; Sri Subanti (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objective of research was to find out: (1) which learning model influenced better student learning achievement among Pair Checks (PC), Teams Assisted Individualization (TAI) or Student Teams Achievement Divisions (STAD), (3) which students had better mathematics learning achievement among those with auditory, visual, or kinesthetic mathematics learning style, (3) in each learning style (auditory, visual, or kinesthetic), which one influenced better mathematics learning achievement in Teams Assisted Individualization (TAI) or Student Teams Achievement Divisions (STAD), (4) in each learning model (Teams Assisted Individualization [TAI] and Student Teams Achievement Divisions [STAD]), which one influenced better mathematics learning achievement towards the students with auditory, visual, or kinesthetic learning style. This study was a quasi experimental research using 2 independent variables (learning model and students’ learning style) and 1 dependent variable (mathematics learning achievement). The data collection was conducted using documentation, test, and questionnaire. Technique of analyzing data used was a 3x3 two-way ANAVA with unbalanced cells. The samples of the research were taken by using the combination of stratified random and cluster random sampling techniques. The result of research showed that: (1) the students given PC learning model had better learning achievement than those given TAI model, those given PC had better learning achievement than those given STAD, while those given TAI and STAD models had equal good learning achievement; (2) the students with auditory and visual learning styles had equal good learning achievement, those with auditory had better learning achievement than those with kinesthetic, and those with visual had better learning achievement than those with kinesthetic; (3) in each learning model, the students with auditory and visual learning styles had equal good learning achievement, those with auditory had better learning achievement than those with kinesthetic, and those with visual had better learning achievement than those with kinesthetic, (4) in each learning style, the students given PC learning model had better learning achievement than those given TAI model, those given PC had better learning achievement than those given STAD, while those given TAI and STAD models had equal good learning achievement.Keywords: Pair Checks, Team Assisted Individualization, and Student Teams Achievement Divisions